Materials towards the study of Vasubandhuʼs Viṁśikā: Sanskrit and Tibetan critical editions of the verses and autocommentary, an English translation and annotations - Vasubandhu ca. 4. Jh. (Harvard oriental series, 2016)
"The Twenty Verses on Manifestation-Only of the Indian Buddhist philosopher Vasubandhu (c. 350-430?), his Viṁśíkā, is one of the most important treatises of the Yogācāra school. Accompanied by the author's own commentary, the text lays out a vision of a Buddhist Idealism in which even one's experience of the sufferings of hell is revealed to be nothing other than the results of working out one's karma. Later scholars commented on the work a number of times, in its original Sanskrit, in Tibetan translation, and in three Chinese versions. This book presents an edition and translation of the Sanskrit text of the core verses, alongside the original author's commentary, based directly on the manuscript evidence. This is accompanied by an edition of the canonical translations of these texts found in the Tibetan Tanjurs, as well as a draft translation of the verses in Tibetan, found in a manuscript from Dunhuang. This publication therefore provides the most reliable and comprehensive philological accounting to date for this fundamental work."--Publisher's web site